Efficacy of liquid‐based genetic diagnosis of endometrial cancer. Issue 12 (26th October 2018) - Matsuura, Motoki; Yamaguchi, Kiyoshi; Tamate, Masato; Satohisa, Seiro; Teramoto, Mizue; Iwasaki, Masahiro; Sugita, Shintaro; Hasegawa, Tadashi; Koubo, Rika; Takane, Kiyoko; Ikenoue, Tsuneo; Furukawa, Yoichi; et al.
Abstract : Although liquid‐based cytology (LBC) has increased the sensitivity of cytological diagnosis of endometrial cancer (EC) compared with conventional smear cytology, the sensitivity of LBC for the detection of EC is between 70% and 96% and remains unsatisfactory. In the present study, we compared the efficacy of LBC with liquid‐based genetic diagnosis (LBGDx) by amplicon sequencing of five genes including PTEN, PIK3CA, CTNNB1, KRAS, and TP53 in 48 LBC subjects who underwent endometrial screening. Consequently, LBC classified 15 samples as "positive or suspicious for malignancy" and the 15 were later confirmed as EC. However, LBC failed to identify five cases who were diagnosed as EC by additional transvaginal ultrasound and endometrial curettage, indicating that the sensitivity of cytology alone was 75% (15/20). LBGDx identified 11 pathogenic PTEN variants in 10 subjects, six PIK3CA variants in nine, three CTNNB1 variants in five, two KRAS variants in four, and three TP53 variants in three. Collectively, at least one pathogenic variant was identified in 19 subjects, which included 17 EC (15 endometrioid carcinoma and 2 endometrial carcinosarcomas), and one cervical adenocarcinoma. However, LBGDx did not identify any pathogenic mutations in three of the 20 EC, indicating that the sensitivity of LBGDx alone was 85% (17/20). Although five EC were negative for malignancy by LBC and three were negative for pathogenic mutations by LBGDx, the combination of LBC and LBGDx would successfully diagnose all 20 EC. These data suggested that LBGDx is a useful strategy to improve the sensitivity of screening of EC by LBC. Abstract : We have shown that liquid‐based genetic diagnosis should be a useful strategy to improve the diagnostic sensitivity and specificity of endometrial screening.